Assessment of Community Banks in Nigeria - Michael T. Marx (Universität zu Köln, Arbeitsstelle für Entwicklungsländerforschung (AEF), 2005)
This study on community banks in Nigeria was undertaken in June 2004 by the FAO Investment Centre, with financial support from the Canadian International Development Agency (CIDA), the Department for International Development (DFID), the International Fund for Agricultural Development (IFAD), the Ford Foundation (FF), the United Nations Development Programme (UNDP) and the World Bank (WB), and in collaboration with the Central Bank of Nigeria (CBN). The objective of the study was to assess the past and present performance of community banks, in particular rural-based banks, and to propose a first framework for their support.
Keywords: 330